The regional turnover of cartilage collagen matrix in late-stage human knee osteoarthritis. Issue 6 (June 2022) - Jørgensen, A.E.M.; Agergaard, J.; Schjerling, P.; Heinemeier, K.M.; van Hall, G.; Kjaer, M.
Summary: Objective: Cartilage collagen has very limited repair potential, though some turnover and incorporation has not been fully excluded. We aim to determine the regional turnover of human osteoarthritis cartilage. Design: Patients scheduled for knee joint replacement surgery due to osteoarthritis were recruited in this prospective study of four weeks duration. Deuterium oxide (D2 O) was administered orally by weekly boluses at 70% D2 O, initially 150 ml followed by three boluses of 50 ml. Cartilage from the medial tibia plateau was sampled centrally, under the meniscus, and from osteophytes and treated enzymatically with hyaluronidase and trypsin. Samples were analysed for deuterium incorporation in alanine using mass spectrometry and for gene expression by real-time reverse transcriptase polymerase chain reaction. Results: Twenty participants completed the study: mean (SD) age 64 ± 9.1 years, 45% female, BMI 29.5 ± 4.8 kg/m 2 . Enzymatically treated cartilage from central and submeniscal regions showed similar enrichments at 0.063% APE, while osteophytes showed significantly greater enrichment at 0.072% APE (95% confidence interval of difference) [0.004–0.015]). Fractional synthesis rates were similar for central 0.027%/day and submeniscal cartilage 0.022%/day but 10-fold higher in osteophytes 0.22%/day [0.098–0.363]. When compared to central cartilage, submeniscal cartilage had increased gene expression of MMP-3 and decreased lubricin expression. Untreated cartilage had higher turnover (enrichments at 0.073% APE) than enzymatically treated cartilage (0.063% APE). Conclusions: In OA, despite regional differences in gene expression, the turnover of the articular cartilage matrix across the entire joint surface is very limited, but higher turnover was observed in osteophyte cartilage.